MULTfflOP MOBILE CELLULAR NETWORK - MOHAMAD HASSAN MUKHTAR, FAIZAL (Universiti Teknologi Petronas, 2005)
Code Division Multiple Access (CDMA) system capacity is interference limited. Distance of the mobile station (MS) to the base station (BS) affects the capacity and interference of a cellular network system. Relaying is to shorter the distance between BS and MS by adding a relay station (RS) between them. Transmission power is smaller due to shorter distance and thus improves the capacityof the CDMAsystem due to reduction in interference. Relaying can be done by using fixed relay station or mobile relay station. Both objectives are to improve the capacity and reduce interference but they are different since fixed relay station is constructed on land or building while mobile relay station is additional features added into mobile phones. This project shows the benefits of multihop with mobile relay station which improve the interference by relaying compared to thesystem without relaying.